Effects of operational parameters on the treatment of nitrate-rich wastewater by autohydrogenotrophic denitrifying bacteria - Mousavi, S.; Ibrahim, S.; Aroua, M.K. (2013)
The effects of the C/N ratio, as well as hydrogen gas and substrate concentrations, on the treatment of nitrate-rich wastewater by autohydrogenotrophic denitrifying bacteria in sequencing batch reactors were investigated. Among the various C/N ratios applied in this study, a C/N ratio of 4 was found to be the most suitable ratio that resulted in faster growth and adaptation. The denitrification rate improved with less accumulation of nitrite with increasing H2 sparging time. Moreover, an increase in nitrate concentration resulted in high nitrite accumulation. The nitrite accumulated to 601mg/L NO2-N when the nitrate concentration was 1000mg/L NO3 —N. The specific degradation rates for nitrate and nitrite were found to be 27.8mg NO3 —N/g MLVSS/d and 50mg NO2 —N/g MLVSS/d, respectively, when the C/N ratio was 2, and H2 as electron donor was sparged for 1min with 2h interval. Â© 2013 CIWEM.